2007
DOI: 10.1038/sj.bjc.6603722
|View full text |Cite
|
Sign up to set email alerts
|

Familial risk for gastric carcinoma: an updated study from Sweden

Abstract: Reliable data on familial risks are important for clinical counselling and cancer genetics. However, the estimates of familial risk of gastric cancer vary widely. We examined the risk of familial gastric cancer using the updated Swedish Family-Cancer Database with 5358 patients among offspring and 36 486 patients among parents. There were 133 families with one parent and one offspring diagnosed with gastric cancer, and 20 families with two affected offspring. Familial standardised incidence ratios (SIRs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 59 publications
(58 reference statements)
1
32
2
1
Order By: Relevance
“…Incidences described range from 2.8% in Sweden to 36.6% in Japan and are different between low-and high-risk areas [4][5][6][7]. Familial gastric cancer can be classified as hereditary diffuse gastric cancer (HDGC), familial intestinal gastric cancer (FIGC) and, when the histopathology of tumours is unknown, as familial gastric cancer (FGC) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Incidences described range from 2.8% in Sweden to 36.6% in Japan and are different between low-and high-risk areas [4][5][6][7]. Familial gastric cancer can be classified as hereditary diffuse gastric cancer (HDGC), familial intestinal gastric cancer (FIGC) and, when the histopathology of tumours is unknown, as familial gastric cancer (FGC) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors, giving rise to high sibling risk in the case of corpus cancer, H. pylori infection may be an important one. The association of upper stomach cancer and esophageal adenocarcinoma in families may also lead to important clues on the aetiology of both diseases [16] .…”
Section: Risk Factors For Familial and Non-familial Gastrointestinal mentioning
confidence: 99%
“…A much higher incidence of familial GC (FGC) was reported from Mediterranean countries [19] , while a relatively low occurrence was noted in northern European countries [14] . Some studies, although not all, showed that a family history of GC might be considered a stronger risk factor for women [2,3] , or that risk of GC might be higher for subjects with an affected sibling rather than a parent [13,15,16,21] . The risk of GC associated with family history for non-GC has been found with different cancers in different studies [5,10,15,21] .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, although not all, showed that a family history of GC might be considered a stronger risk factor for women [2,3] , or that risk of GC might be higher for subjects with an affected sibling rather than a parent [13,15,16,21] . The risk of GC associated with family history for non-GC has been found with different cancers in different studies [5,10,15,21] . In addition, the histological type of FGC was pronounced for "intestinal" and/or "diffuse" cancers in different studies germline mutation of CDH1, has never been found in eastern Asia [8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation